Monitoring vegetation changes using the NDVI index in Baghdad Governorate (Journal of the College of Basic Education, 2024)
This study dealt with (monitoring vegetation cover changes using the NDVI index in Baghdad governorate) by employing and analyzing satellite visuals. The oldest satellite visualization was used from the year (1984) to (2022) in the study area and measuring the change of vegetation cover for every (10) years and for five periods. For the winter and summer seasons, this study concluded that there was a clear change in the vegetation cover during the mentioned period for all cultivars, according to what was mentioned in the satellite visual. In the dense vegetation cover and the rule of barren lands in the study area due to climatic changes and some human actions